Facade deterioration at shop houses in The Royal Town of Klang / Rubiyatul Adawiah Ab Haris - Ab Haris, Rubiyatul Adawiah (Faculty of Architecture, Planning and Surveying, 2015)
The facade is the front of the building. In front of the building architecture means seem the most prominent. Construction of buildings, characterized by a modern design affects the appearance of the city as well as threatening to the potential areas to be classified as a heritage area. The effects of changes in the facade of the building is also an issue that is rarely highlighted as they are unaware of the opinion of the local community will privilege on a monument or historical building located in the area. The approach used in this study is the observation in the study area to identify issues and problems found in the study area. Therefore, based on this situation, a study on the facade of the building and the role of conservation measures put forward and seek the best resolution in tackling the problem as it gives visual impact to the formation of the image of a city.